Penegakan Hukum yang Dilakukan Direktorat Lalu Lintas Polda Bali terhadap Pelanggaran Kendaraan Roda Tiga Angkutan Sampah Melebihi Daya Beban Angkut di Kota Denpasar - I Gede Eka Surya Pramana; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2022)
The Denpasar city government has created a garbage collection program that is managed by the Banjar. The waste produced in 2021 is around 550 - 600 tons every day. To reduce waste, we formed a team to store the waste and transport it to the landfill using a three-wheeled motorbike. The method of empirical research is used in conducting this research, with legal research being useful to see the legal point of view in the real conditions of a fact that exists in society. The conclusion of this study is that the Denpasar city government program to transport waste to the TPA for three-wheeled motorized vehicles is less efficient because the amount of waste carrying capacity exceeds the limit, thereby endangering other vehicles. The Traffic Directorate of the Bali Police carried out two types of efforts to reduce the number of violations by means of prevention and action.